ANALISIS IDENTIFIKASI DAN PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN WILAYAH DI KABUPATEN CILACAP - Ropingi, Ropingi; Agustono, Agustono; Yuliani, Triasih (Universitas Muhammdaiyah Surakarta, 2009)
This study aimed to identify agriculture sector and sub-sector for region developing; to know of role of agriculture sector and sub-sector for region developing in Cilacap Regency. The used descriptive method, then the data analyze were Location Quotient (LQ) Approach, Income Multiplier effect, and Labour Multiplier effect. The research used secondary data, it was Gross Domestic Regional Product of Central Java and Gross Domestic Regional Product of Cilacap Regency based on 2000 constant price along the year of 1999 to 2003 and the labor of Cilacap Regency. The result of the research shows: the basic sectors of Cilacap Regency are manufacture industry, trading, hotel and restaurant sector. The contribution of agriculture sector in Cilacap Regency can be known from the Income Multiplier Effect along the year of analysis. In the labor side shows that the capacity of agriculture employment field more increase and so does the contribution of agriculture sector for the employment in Cilacap Regency.